Predictive value of myosteatosis and subcutaneous adipose tissue on the prognosis of ESCC patients undergoing chemoradiotherapy - Ling Xiao; Yudi Liu; Xue Zhang; Xinyu Nie; Jiahua Lyu; Tao Li (Scientific Reports)
Abstract The relationship between CT-based body composition parameters and chemoradiotherapy outcomes in patients with esophageal squamous cell carcinoma (ESCC) is unclear. This study aimed to clarify the predictive value of myosteatosis and subcutaneous adipose tissue area (SATA) in ESCC patients undergoing chemoradiotherapy. The study cohort consisted of 255 ESCC patients undergoing chemoradiotherapy between January 2012 and December 2018. Body composition parameters, such as mean muscle density in Hounsfield units (HU) and adipose tissue area at the third lumbar vertebra (L3) level, were quantified on CT scans. Hazard ratios were estimated to establish the relationship between pretreatment skeletal muscle density (preSMD) and adipose tissue area with the overall survival (OS) rate. Optimal stratification was utilized to set threshold values. Kaplan–Meier plots and Cox proportional hazards models were developed to analyze survival distributions. Among 255 ESCC patients who received chemoradiotherapy, the median survival time was 24.3 months (95% CI 20.33–33.8). Multivariate analysis revealed that tumor length (HR = 1.547; 95% CI 1.115–2.145; P = 0.009), clinical stage (HR = 5.696; 95% CI 2.053–15.798; P < 0.001), and preSMD (HR = 1.528; 95% CI 1.079–2.169; P = 0.017) were independent indicators for OS. Additionally, SATA emerged as an independent predictor of preSMD (HR = 0.991; 95% CI 0.986–0.996; P = 0.038). A nomogram integrating preSMD, pretreatment subcutaneous adipose tissue area (preSATA), and independent prognostic factors effectively predicts the prognosis of ESCC patients, supplementing the TNM staging system. The study suggests that a prognostic model combining preSMD and preSATA effectively predicts the prognosis of ESCC patients undergoing chemoradiotherapy.